In silico identification and structure function analysis of a putative coclaurine N-methyltransferase from Aristolochia fimbriata. (April 2020) - Ali, Roshan; Jiao, Yuannian; Kerr Wall, P.; Patching, Simon G.; Ahmad, Irshad; Lutfulla, Ghosia; dePamphilis, Claude W.
Graphical abstract: Highlights: Analysis of a coclaurine N -methyltransferase from the basal angiosperm A. fimbriata . CNMTs are central enzymes in the biosynthesis of ethnopharmacological compounds. Computational tools were used to predict a three-dimensional homology model. Also to investigate the function of the protein and its mechanism for methylation. CNMT activity follows an SN2-type mechanism involving residues Tyr79 and Glu96. Abstract: In this study we isolated and performed in silico analysis of a putative coclaurine N -methyltransferase (CNMT) from the basal angiosperm Aristolochia fimbriata . The Aristolochiaceae plant family produces alkaloids similar to the Papavaraceae family, and CNMTs are central enzymes in biosynthesis pathways producing compounds of ethnopharmacological interest. We used bioinformatics and computational tools to predict a three-dimensional homology model and to investigate the putative function of the protein and its mechanism for methylation. The putative CNMT is a unique ( S )-adenosyl- L -methionine (SAM)-dependent N -methyltransferase, catalyzing transfer of a methyl group from SAM to the amino group of coclaurine. The model revealed a mixed α/β structure comprising seven twisted β-strands surrounded by twelve α-helices. Sequence comparisons and the model indicate an N-terminal catalytic Core domain and a C-terminal domain, of which the latter forms a pocket for coclaurine. An additional binding pocket for SAM is connected to the coclaurine binding pocket by a small opening. CNMT activity is proposed to follow an SN 2-type mechanism as observed for a similarly conformed enzyme. Residues predicted for the methyl transfer reaction are Tyr79 and Glu96, which are conserved in the sequence from A. fimbriata and in homologous N -methyltransferases. The isolated CNMT is the first to be investigated from any basal angiosperm.